1980
DOI: 10.1530/acta.0.0950212
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian steroid secretion in normally menstruating women I. The contribution of the developing follicle

Abstract: In 9 normally menstruating women undergoing surgical sterilization by tubal ligation the levels of a dozen steroids were measured in the blood from the peripheral and both ovarian veins before and after the enucleation of the largest follicle. In addition, the peripheral levels of progesterone, 17-hydroxyprogesterone, oestradiol and oestrone were measured during 3 pre\x=req-\ operative and 3 post-operative days. Compared to their levels in peripheral blood, the levels of pregnenolone, 17-hydroxypregnenolone, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 11 publications
5
9
0
Order By: Relevance
“…However, the higher serum cortisol levels may be due to the stress of laparoscopy (30) or to rapid diffusion of the cortisol present in FF into surrounding tissues (13). Furthermore, Dehennin et al (11) have shown the presence in the human ovarian follicle of 21-hydroxylase and 11/i-hydroxylase activity, suggesting local synthesis, and corroborating the findings of Aebo et al (31). It seems, therefore, that FF cortisol is probably derived from both mechanisms.…”
Section: Discussionsupporting
confidence: 57%
“…However, the higher serum cortisol levels may be due to the stress of laparoscopy (30) or to rapid diffusion of the cortisol present in FF into surrounding tissues (13). Furthermore, Dehennin et al (11) have shown the presence in the human ovarian follicle of 21-hydroxylase and 11/i-hydroxylase activity, suggesting local synthesis, and corroborating the findings of Aebo et al (31). It seems, therefore, that FF cortisol is probably derived from both mechanisms.…”
Section: Discussionsupporting
confidence: 57%
“…The relevant data are compiled in Table 1 ; the laboratory investigations carried out to ascertain normal liver and kidney function were de¬ scribed in a previous paper (Aedo et al 1980). The methods for the estimation of the day of the menstrual cycle and the surgical procedure employed were the same as in the previous paper.…”
Section: Methodsmentioning
confidence: 99%
“…The notifications Ai, Bi, Ci refer to the samples obtained before and A2, B2, C2 to those obtained after enucleation of the corpus luteum. As in the previous study (Aedo et al 1980) all blood samples were withdrawn from both ovaries approximately at the same time by a team of two surgeons. The time elapsing between the removal of the corpus luteum and the withdrawal of the second blood sample varied between 12-30 min (mean: 17.1 min).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations